Identification of Active Compounds From Yi Nationality Herbal Formula Wosi Influencing COX-2 and VCAM-1 Signaling - Liu, Yuan; Luo, Pei; Zhang, Ji-Zhong; Chen, Xiao-Yi; Li, Li-Min; Wu, You-Jiao; Yin, Qiao-Zhi; Huang, Li (Frontiers in Pharmacology, 2020)
The Yi nationality herbal formula Wosi is used in China as a folk medicine to treat arthritis and related diseases. Despite its widespread use, the active ingredients, and pharmacological mechanisms are not performed. This is the first time to identify the active compounds from Wosi with the aim at providing the potential effect of Wosi and exploring its underlying anti-inflammatory mechanism in MSU-induced arthritis rats. In this study, anti-hyperuricemia effect was assessed by reducing the serum uric acid levels and increasing uric acid excretion in the urine for the hyperuricemia rat model. Wosi significantly suppressed the degree of joint swelling and improved the symptoms of inflammation induced by MSU crystals. The inhibition of IL-2, IL-1β, IFN-γ, and IL-6 secretion and IL-10 increase in the serum were also observed. This study also focuses on the screening of the main compounds from Wosi against cyclooxygenase for anti-inflammatory properties using molecular docking. The result showed 3-O-[α-L-pyran rhamnose(1-3)-β-D-pyran glucuronic acid]- oleanolic acid, 3-O-(β-D-pyran glucuronic acid)-oleanolic acid-28-O-β-D-pyran glucoside, and 3-O-[α-L-pyran rhamnose(1-3)-β-D-pyran glucuronic acid]-oleanolic acid-28-O-β-D-pyran glucoside with a higher binding affinity than the standard ligand with COX-2 (co-crystallized ligand) which indicated relatively higher interaction than COX-1. The preferential selectivity toward inhibiting COX-2 enzyme over COX-1 of three compounds from Wosi were evaluated using in-vitro cyclooxygenases 1 and 2 (COX-1/2) inhibition assays. Meanwhile, the down-regulated protein expression of COX-2 and VCAM-1 in synovial tissue sections from ankle joints of experiments rats were confirmed by immunohistochemistry analysis after the Wosi treatment. In conclusion, three oleanolic acid glycosides were implied as mainly efficient compounds in Yi nationality herbal formula Wosi for arthritis therapy via selectively influencing COX-2 and VCAM-1 signaling.